Rapid point-of-care CD4 testing at mobile units and linkage to HIV care: an evaluation of community-based mobile HIV testing services in South Africa - Rosa Sloot; Mary T. Glenshaw; Margaret van Niekerk; Sue-Ann Meehan (BMC, 2020)
Abstract Background Mobile HIV testing services (HTS) are effective at reaching undiagnosed people living with HIV. However, linkage to HIV care from mobile HTS is often poor, ranging from 10 to 60%. Point-of-care (POC) CD4 testing has shown to increase retention in health facilities, but little evidence exists about their use in mobile HTS. This study assessed the feasibility of POC CD4 test implementation and investigated linkage to HIV care among clients accepting a POC test at community-based mobile HTS. Methods This retrospective study used routinely collected data from clients who utilized community-based mobile HTS in the City of Cape Town Metropolitan district, South Africa between December 2014 and September 2016. A POC CD4 test was offered to all clients with an HIV positive diagnosis during this period, and a CD4 cell count was provided to clients accepting a POC CD4 test. Random effects logistic regression was used to assess factors associated with POC CD4 test uptake and self-reported linkage to care among clients accepting a POC test. Models were adjusted for sex, age, previous HIV test done, tuberculosis status and year of HIV diagnosis. Results One thousand three hundred twenty-five of Thirty-nine thousand seven hundred ninety clients utilizing mobile HTS tested HIV positive (3%). 51% (679/1325) accepted a POC test. The age group with the highest proportion accepting a POC test was 50+ years (60%). Females were less likely to accept a POC test than males (odds ratio = 0.7, 95%CI = 0.6-0.8). Median CD4 count was 429 cells/μl (interquartile range = 290-584). Among 679 clients who accepted a POC CD4 test, 491 (72%) linked to HIV care. CD4 cell count was not associated with linkage to care. Conclusion Our findings suggest that mobile HTS can identify early HIV infection, and show that a high proportion of clients with a POC test result linked to care. Future research should assess factors associated with POC test acceptance and assess the impact of POC CD4 testing in comparison to alternative strategies to engage HIV positive people in care.